Development of a genoserotyping method for salmonella infantis detection on the basis of pangenome analysis - Yang, Seung Min; Baek, Jiwon; Kim, Eiseul; Kim, Hyeon Be; Ko, Seyoung; Kim, Donghyuk; Yoon, Hyunjin; Kim, Hae Yeong (Microorganisms, 2021)
In recent years, Salmonella Infantis has become a predominant serovariant in clinical and poultry isolates, thereby imposing a substantial economic burden on both public health and the livestock industry. With the aim of coping with the steep increase in serovar Infantis prevalence, a polymerase chain reaction (PCR)-based rapid and accurate diagnostic assay was developed in this study through pangenome profiling of 60 Salmonella serovars. A gene marker, SIN_02055, was identified, which is present in the S. Infantis genome but not in the pangenome of the other serovars. Primers specific to SIN_02055 were used to accurately detect serovar Infantis, and to successfully differentiate Infantis from the other 59 serovars in real-time PCR with a R2 of 0.999 and an efficiency of 95.76%. The developed method was applied to 54 Salmonella strains belonging to eight dominant serovars, and distinguished Infantis from the other seven serovars with an accuracy of 100%. The diagnostic primer set also did not show false positive amplification with 32 strains from eight non-Salmonella bacterial species. This cost-effective and rapid method can be considered an alternative to the classic serotyping using antisera.
Keywords: Genoserotyping; Pangenome; Real-time PCR; Salmonella Infantis